Productivity and income effect of breast cancer among women in Southwestern Nigeria - Josue Mbonigaba; Wilfred Gbenga Akinola (Economies, 2021)
Women's breast cancer (BC) in Africa is detrimental to development, given the role women play in their families and society's well-being. Policymakers should be alerted to the effects of BC. This paper describes the income impact of breast cancer and assesses factors that influence income and productivity among women with BC. Cross-sectional data were collected using questionnaires on 200 women with clinically confirmed BC cases in Southwest Nigeria over 6 months. About sixty-one percent (61.5%) of the women with clinically confirmed BC cases were self-employed, 62% were absent at the workplace for 7 days, indicating that 31.8% suffered productivity loss at the workplace on average. Sixteen percent of women in the group were absent at the workplace for an average of 10 days, showing a 45.5% productivity loss at the workplace. Lastly, 22% of the women were absent at the workplace for more than 2 weeks on average. An increasing incidence of BC among women causes a 26.2% decrease in productivity level at the workplace. The results from simple linear regression corroborate the findings from the descriptive statistics that BC has a significant but inverse effect on women's income and productivity. It showed that an increase in the number of confirmed cases of BC will decrease economic impact and productivity by 13.5% and 19.5%, respectively. These findings urgently call for the attention of the policymakers.
Keywords: 1; I12; I11; 330; breast cancer; income effects; productivity effect; women